Adding-on Phenomenon After Surgery in Lenke Type 1, 2 Adolescent Idiopathic Scoliosis: Is it Predictable?. Issue 8 (April 2016) - Yang, Changwei; Li, Yanming; Yang, Mingyuan; Zhao, Yunfei; Zhu, Xiaodong; Li, Ming; Liu, Gabriel
Abstract : Study Design: A retrospective study. Objective: The aim of this study was to detect risk factors for Adding-on after posterior correction surgery in patients with Lenke 1 or 2 AIS, and to explore whether Adding-on Index could be used to predict Adding-on effectively. Summary of Background Data: Adding-on phenomenon is a common complication in Lenke 1 or 2 AIS patients after correction surgery. However, whether it can be predicted after surgery remains unknown. Methods: Lenke 1 or 2 AIS patients receiving correction surgery in our center from January 2009 to July 2013 were analyzed. Antero-posterior and lateral films were evaluated before surgery, at 2 weeks' and 2 years' follow-up. Patients were divided into 2 groups according to whether Adding-on occurred at the 2 years' follow-up. Risk factors of Adding-on were analyzed, and Adding-on Index was proposed and verified. Results: Sixteen patients (16.3%) suffered from distal Adding-on at 2-year follow-up. Several parameters were found to be significantly different between 2 groups, including Risser's sign, postoperative Cobb angle of main thoracic, postoperative Cobb angle of main thoracic curve at 2-year follow-up, preoperative and postoperative Cobb angle of lumbar curve, postoperative Cobb angle of lumbar curve at 2-year follow-up, LIV-EV, LIV-SV, LIV-CSVL, LAV-CSVL, LAV-LIV, DnfS, and postoperative TJK. No significant differences in SRS-22 scores were observed. Binary logistic regression analysis showed that DnfS and postoperative residual Cobb angle of lumbar curve were primary factors for occurrence of Adding-on. According to the regression equation, Adding-on Index was defined as 4 × DnfS-postoperative lumbar curves Cobb angle. On the basis of ROC curve, if Adding-on Index was more than 12, the occurrence rate of Adding-on was 88%. On the contrary, the rate of no Adding-on phenomenon was 80%. Conclusion: DnfS and posterior Cobb angle of lumbar curve were 2 important factors for Adding-on in Lenke 1, 2 AIS patients. Adding-on Index can be used to predict the occurrence of Adding-on effectively. Level of Evidence: 4